Long-Term Cancer Recurrence Rates following Nipple-Sparing Mastectomy: A 10-Year Follow-Up Study. (28th September 2022) - Boyd, Carter J.; Salibian, Ara A.; Bekisz, Jonathan M.; Axelrod, Deborah M.; Guth, Amber A.; Shapiro, Richard L.; Schnabel, Freya R.; Karp, Nolan S.; Choi, Mihye
Abstract : Background: Despite the increased use of nipple-sparing mastectomies, there are limited data examining long-term cancer recurrence rates in these patients. The objective of this study was to analyze breast cancer recurrence in patients who underwent therapeutic nipple-sparing mastectomy with a median of 10 years of follow-up. Methods: All patients undergoing nipple-sparing mastectomy at a single institution were retrospectively reviewed temporally to obtain a median of 10 years of follow-up. Patient demographic factors, mastectomy specimen pathologic findings, and oncologic outcomes were analyzed. Univariate analysis was performed to identify independent risk factors for locoregional recurrence. Results: One hundred twenty-six therapeutic nipple-sparing mastectomies were performed on 120 patients. The most frequently observed tumor histology included invasive ductal carcinoma (48.4 percent) and ductal carcinoma in situ (38.1 percent). Mean tumor size was 1.62 cm. Multifocal or multicentric disease and lymphovascular invasion were present in 31.0 percent and 10.3 percent of nipple-sparing mastectomy specimens, respectively. Sentinel lymph node biopsy was performed in 84.9 percent of nipple-sparing mastectomies, and 17.8 percent were positive. The rate of positive frozen subareolar biopsy was 7.3 percent ( n = 82) and that of permanent subareolar pathology was 9.5 percent ( n = 126). The most frequently observed pathologic tumor stages were stage I (44.6 percent) and stage 0 (33.9 percent). The incidence of recurrent disease was 3.17 percent per mastectomy and 3.33 percent per patient. On univariate analysis, no demographic, operative, or tumor-specific variables were independent risk factors for locoregional recurrence. Conclusions: Overall recurrence rates are low in patients undergoing nipple-sparing mastectomy at a median follow-up of 10-years. Close surveillance should remain a goal for patients and their providers to promptly identify potential recurrence. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.